Faktor-Faktor Yang Mempengaruhi Dividend Policy Pada Perusahaan Manufaktur - Steven Kent, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The objective of this study is to determine the effect of profitability, leverage, firm size, free cash flow, audit committee and board of commissioners toward the dividend policy. This research uses data from manufacturing companies listed on the Indonesia Stock Exchange during 2015 – 2018. Sample was selected using purposive sampling and amounted to 46 companies. Data was processed by E-views 10. The results of this result indicate that free cash flow has positive significant effect on dividend policy. Leverage, Firm Size, Free Cash Flow, Audit Committee and Board of Commissioners have no significant effect on dividend policy.